2015
DOI: 10.1021/acs.energyfuels.5b00676
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Gasification of in Situ/ex Situ Coal Char with CO2 in a Micro Fluidized Bed Reaction Analyzer

Abstract: The so-called micro fluidized bed reaction analyzer (MFBRA) was adopted to implement the isothermal gasification of in situ coal char with CO 2 under minimized external diffusion inhibition. It was done by keeping the reaction atmosphere and temperature in the MFBRA for both coal pyrolysis and char gasification. This was further compared to the gasification of two other kinds of ex situ chars. While the gasification of ex situ char 1 referred to the coal pyrolysis in Ar and then CO 2 gasification of the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…As can be seen from the figure, the final equilibrium mass and time are found to be dependent on temperature. The reaction rate is shown to be faster at higher temperatures for both biomass samples [61]. Note that above 550 °C the equilibrium condition mass of ARTOK was always lower than the AROK, since the oxidation of carbon in the char takes place parallel to thermal decomposition and release of volatile matter [62].…”
Section: Kinetic Parametersmentioning
confidence: 88%
“…As can be seen from the figure, the final equilibrium mass and time are found to be dependent on temperature. The reaction rate is shown to be faster at higher temperatures for both biomass samples [61]. Note that above 550 °C the equilibrium condition mass of ARTOK was always lower than the AROK, since the oxidation of carbon in the char takes place parallel to thermal decomposition and release of volatile matter [62].…”
Section: Kinetic Parametersmentioning
confidence: 88%
“…In recent years, micro-fluidized bed (MFB) has attracted more attention due to its fast screening and process-intensifying properties [4,5]. Therefore, MFB has been applied to different areas such as solid processing [6,7], chemical conversions [8][9][10], CO 2 capture [11], wastewater treatment [12,13], bioproduction [14,15], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to TGA, the MFBRA features: (1) high rates of heat and mass transfer, (2) capability of online instantaneously pulse feeding and super‐fast heating of powder reactant to bed temperature, (3) negligible external diffusion inhibition, and (4) fast on‐line measurement 19,20 . Until now, it has been successfully applied to study the mechanisms and kinetics of a variety of gas–solid reactions, including pyrolysis, 22–24 gasification, 14,25,26 combustion 27,28 of coal, biomass, oil shale and chars, calcination, 11,20 and reduction 29–32 of various materials as well as catalytic gas–solid reactions, 33,34 etc. These applications have demonstrated that MFBRA is effective, reliable, and adaptable to various gas–solids reactions.…”
Section: Introductionmentioning
confidence: 99%